Sportif: Study of Sports Education and Health - Rahmat Purnomo (Journal of Salutare, 2024)
Sports and physical health education plays a strategic role in the formation of healthy and fit individuals, both physically and mentally. Along with the increasing recognition of the importance of physical education as a key instrument in human resource development, its implementation in various countries, including Indonesia, still faces various challenges. This study aims to identify challenges and opportunities in sports and physical health education in Indonesia. Using quantitative and qualitative approaches, this study involved 300 students and 50 teachers from 10 schools in five provinces, with stratified random sampling techniques. Data were collected through questionnaires and in-depth interviews, as well as quantitative analysis using descriptive statistics and linear regression, and qualitative analysis through content analysis techniques. The results of the study indicate that challenges in physical education involve aspects of curriculum, infrastructure, and students' low perceptions of the importance of physical education. The gap between urban and rural areas and differences in participation based on gender are key issues. In addition, the use of technology in teaching methods needs to be improved, while the rigid curriculum must be reformulated to integrate mental and social health. This study suggests the need for deep policy reform to ensure that physical education does not only function for physical fitness, but also as a medium for creating a more inclusive and healthy society. With joint efforts from the government, schools and the community, it is hoped that physical education can make a more significant contribution to the health and well-being of the younger generation.